Socio-Economic Impact Of Converting Agricultural Land To Nickel Mining Industrial Land In Labota Village, Bahodopi District, Morowali Regency - Nurfaida; Yusna Indarsyih; Muhammad Aswar Limi (International Journal of Technology and Education Research, 2025)
This study aims to determine 1) To determine the social impact of the conversion of agricultural land to nickel mining industry land in Labota Village, Bahodopi District, Morowali Regency, 2) To determine the economic impact of the conversion of agricultural land to nickel mining industry land in Labota Village, Bahodopi District, Morowali Regency. This study started from July to August 2024. The data in this study used secondary and primary data obtained through documentation methods, library studies and interviews, the study used quantitative and qualitative methods in solving problems. The results of the analysis show 1) the social impact of the conversion of agricultural land to nickel mining industry has caused major changes in the social structure of the Labota village community. 2) Economically, the conversion of agricultural land has a fairly positive impact on community income. The income change index value of 328.08% indicates that after the conversion of agricultural land to nickel mining industry land, the income of the Labota Village community has increased significantly. In detail, the community's income after the land conversion is more than three times (around 3.28 times) compared to their income before the change. Many people who previously relied on agriculture for their livelihoods have now shifted to mining and other sectors, such as trade and entrepreneurship, which have increased their incomes. However, this economic impact has also been accompanied by a reduction in agricultural land ownership. Many people have sold their land to mining companies, reducing the amount of productive land previously owned by farmers. This has the potential to reduce food security in villages and impact the sustainability of the agricultural sector.